Redescription of Heizmannia (Heizmannia) chandi Edwards (Diptera: Culicidae) - Tewari, S. C.; Krishnamoorthy, R.; Ayanar, K.; Munirathinam, A.; Venkatesh, A.; Tyagi, B. K. (Zootaxa, 2012)
Barraud (1934) described very briefly genus Heizmannia Ludlow as consisting of nine species including Heizmannia (Heizmannia) chandi Edwards. Most of the characters used in describing the species emphasized the male genitalia, based on which a diagnostic and illustrated key of adults was constructed of these nine species. Subsequently, however, the genus Heizmannia was extensively revised by Mattingly (1957, 1970) and Thurman (1959) from Southeast Asia. They included 20 species by introducing one new subgenus Mattinglyia. However, in Mattingly’s review (1970) Heizmannia (Heizmannia) chandi and Hz. (Mattinglyia) discrepans Edwards were not included. Tewari et al.(1986) re-described Hz. (Mat.) discrepans but Hz. chandi remained poorly described. In the present paper we are re-describing the adult male and female of Hz. (Hez.) chandi in detail, with emphasis on the male genitalia and variations observed in comparison to the original description of Barraud (1934).